Prevalence and Pattern of smoking behaviour among health workers in Ibadan (2000)
This study is a descriptive survey and utilized purposive and snowball sampling techniques. The modified version of Akinboye (1984). Smoking Behaviour Assessment scale was the instrument used for data collection. Some of the determinants of smoking behaviour reported by the respondents included: to relax, to avoid boredom; to cope with task, and to suppress frustration. Among their major complaints are tiredness, coughing, nervousness and loss of concentration. Out of the 50 respondents who volunteered to participate in this study, about 50 percent were willing to quit smoking and showed intention to enlist in any tobacco cessation or counselling programme. We also found out that religion may have significant influence in tobacco cessation programme for the respondents, as nearly all of them desired divine help. They also believed that they needed social support from their spouses and religious leaders to quit smoking. Based on the findings of this study, there is need for a national tobacco behaviour survey among Nigerians health workers and adolescents. There is also the need for the inauguration of tobacco cessation counselling programme in the country